Memercayai Alkitab Sebagai Firman Allah Yang Benar - Saenom Saenom; Marthen Mau (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
Believing in the Bible as the true word of God without having a sense of doubt becomes an absolute standard because the word of God is a word that is not only true but perfect. The Word of God is said to be perfect because the source of inspiration and the main Author is God who gave the true words to be written by the writers of the word that He wanted. A certain group or some people may doubt the Bible as the word of God or consider the Bible as an old book that is no longer relevant to today's developments. This research aims to narrate the Bible as the true word of God and is very relevant to the development of technology in this era. The research methodology used for research and writing is qualitative methodology and literature. The findings show that the Bible is the true and perfect word of God, so that it cannot be doubted by anyone, be it theologians, historians, scientists, psychologists, psychiatrists or ordinary people